LANGUAGE, COMMUNICATION AND MARKETING: CONTEXUALIZING THE USE OF SHENG LANGUAGE IN ADVERTISING IN KENYA. - MURIUKI, ROBERT G.M. (IJRDO - Journal of Business Management, 2015)
This paper discusses the impact of Sheng language on advertising and marketing in Kenya. The paper observes the evolvement of Sheng as a language in Kenya and its growing importance in advertising and marketing. I will use secondary data to shed more light on the use of Sheng language in advertising in Kenya to contribute to knowledge and awareness on the issue. While at first Sheng was dismissed as a language of the lowly, underprivileged urban youth, it has grown to a language of commerce, social discourse, and politics. This has made advertisers realize that they just have to embrace it to reach the youth who are the potential and actual consumers of goods and services. With the population of youth estimated at 60%, it is a segment that advertisers cannot afford to ignore. The youth represent a significant demographic; -well educated, high spending and care-free. Their consumption habits are exploited by advertisers and marketers to tap them using the Sheng language with simple, catchy and memorable messages.